Faktor yang Berhubungan dengan Siklus Menstruasi pada Siswi SMA Negeri 12 Maros - Selviana, Selviana (An Idea Health Journal, 2021)
Menstruation is said to be a natural process that will occur in every teenager, where the process of removing blood indicates that the organs in the womb are functioning properly.